Suite francesa - Némirovsky, Irène 1903-1942; Dibb, Saul; Speak Up (DVD (Speak Up), 2015)
During the early years of Nazi occupation of France in World War II, romance blooms between Lucile Angellier (Michelle Williams), a French villager, and Bruno von Falk (Matthias Schoenaerts), a German soldier.